2014
DOI: 10.1179/1476830514y.0000000151
|View full text |Cite
|
Sign up to set email alerts
|

Green tea and vitamin C ameliorate some neuro-functional and biochemical signs of arsenic toxicity in rats

Abstract: Natural antioxidants might be useful in the protection of the central nervous system against the toxicity of oral As.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Changes in antioxidant parameters and peroxidation of membrane lipids under arsenic exposure have been documented in animal models [37,38]. Moreover, the ROS generated by arsenic are known to destabilize cell membranes via lipid peroxidation, which is a basic cellular deteriorating process in the liver [2].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in antioxidant parameters and peroxidation of membrane lipids under arsenic exposure have been documented in animal models [37,38]. Moreover, the ROS generated by arsenic are known to destabilize cell membranes via lipid peroxidation, which is a basic cellular deteriorating process in the liver [2].…”
Section: Discussionmentioning
confidence: 99%
“…Ivanov et al 11 demonstrated that AsA from green tea extracts could inhibit atherogenesis. In rats, AsA derived from green tea could help protect against the toxic effects of orally ingested arsenic and improve cellular antioxidative effects 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of epigenetic heterogeneity of developmentally important genes has important implications for assisted reproduction outcomes [34]. Another significant role was observed in the epigenetic regulation of stress reactivity in humans [35] and the formation and maintenance of memory in plasticity genes [36]. …”
Section: Discussionmentioning
confidence: 99%